2020
DOI: 10.1080/13546805.2020.1713736
|View full text |Cite
|
Sign up to set email alerts
|

Similar impairments shown on a neuropsychological test battery in adolescents with high-functioning autism and early onset schizophrenia: a two-year follow-up study

Abstract: Introduction: Cognitive impairments are common in both Autism Spectrum Disorders (ASD) and schizophrenia, but it is unclear whether the pattern of difficulties is similar or different in the two disorders. This cross-sectional and longitudinal study compared the neuropsychological functioning in adolescents with ASD with adolescents with Early Onset Schizophrenia (EOS). Methods: At baseline and at two-year follow-up, participants were assessed with a brief neuropsychological test battery measuring executive fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
1
4
0
1
Order By: Relevance
“…We compared, ASD, SSD and typically developing adult groups on the DLS and executive functioning. In line with past evidence that shows difficulties in executive functioning, i.e., inhibition, organization, planning, and goal-directed behavior in both ASD and SSD (de Boer et al, 2014;Øie et al, 2020;Shi et al, 2020;Yon-Hernández et al, 2022a), we expect to find a significant correlation between the deficits in EFs and low DLS in both groups. Our study attempts to clarify to what extent the presence of these difficulties in EF affects DLS in both conditions.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…We compared, ASD, SSD and typically developing adult groups on the DLS and executive functioning. In line with past evidence that shows difficulties in executive functioning, i.e., inhibition, organization, planning, and goal-directed behavior in both ASD and SSD (de Boer et al, 2014;Øie et al, 2020;Shi et al, 2020;Yon-Hernández et al, 2022a), we expect to find a significant correlation between the deficits in EFs and low DLS in both groups. Our study attempts to clarify to what extent the presence of these difficulties in EF affects DLS in both conditions.…”
Section: Introductionsupporting
confidence: 91%
“…Also, the two conditions share many symptoms. While schizophrenia is characterized by a combination of positive symptoms (delusions and hallucinations), negative symptoms (anhedonia, apathy, social withdrawal) and cognitive symptoms (disorganized thinking, memory difficulties, altered cognitive control) ( American Psychiatric Association, 2013 ; Trevisan et al, 2020 ; Ribolsi et al, 2022 ), the negative symptoms, such as impaired social reciprocity, nonverbal communication difficulties, limited gestures, restrictive and repetitive behaviors, social–emotional communication deficits, sensory abnormalities, poor adaptive behavior are also found in ASD ( Spek and Wouters, 2010 ; Wouters and Spek, 2011 ; Fitzgerald, 2012 ; Øie et al, 2020 ). The presence of these symptoms in both disorders could lead to misdiagnosis in some ASD cases.…”
Section: Introductionmentioning
confidence: 99%
“…Studies comparing neurocognition between patients with ASD and those with schizophrenia-generally, almost all of those studies included clinically stable patients-showed that these two patient groups were comparably impaired overall, although other studies reported inconsistent results in terms of specific domains ( Eack et al, 2013 ; Marinopoulou et al, 2016 ; Øie et al, 2020 ). Our present finding that the remitted patients with a high degree of clinical stability had almost the same level of neurocognitive impairment as the ASD patents except for verbal learning, is in line with the previous studies ( Eack et al, 2013 ; Marinopoulou et al, 2016 ; Øie et al, 2020 ). Furthermore, it seems that our remitted patients with slightly but significantly lower levels on several MCCB domains are similar to a schizophrenia group identified in a recent meta-analysis showing slightly more deficits in several specific cognitive domains ( Kuo and Eack, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…While each of these NDDS has some unique behavioral features, they can also share behavioral impairments, such as alterations in social functioning, impulsivity, and executive function deficits [29,[334][335][336][337][338][339][340][341][342][343][344][345][346][347][348][349]. Cognitive/executive function deficits are also common in NDGDS (AD [350,351], PD [352,353], MS [354][355][356][357], ALS [358][359][360][361][362]), as are alterations in social behaviors [363][364][365] and manifestations of impulsive-like behaviors [366][367][368][369][370].…”
Section: Shared Features Of Neurodevelopmental Disorders and Neurodeg...mentioning
confidence: 99%